Measuring the Effects of Usability Recommendations for Mobile Instant Messaging Apps on User Performance and User Behaviour, International Journal of Human–Computer Interaction - Caro-Alvaro, Sergio; García-López, Eva; García-Cabot, Antonio; Mavri, Aekaterini (My University, 2024)
Researchers worldwide have extensively investigated the influence of Human-Computer Interaction (HCI) on Mobile Instant Messaging applications, exploring aspects such as usability issues and user behaviour. However, traditional HCI challenges remain in these applications today (ie, usability issues and lack of specific usability guidelines). In this paper, we present a contextual and methodological contribution measuring user performance (with a controlled experiment on a set of structured tasks following a within-subjects design) and user behaviour (with a user satisfaction questionnaire) on Mobile Instant Messaging applications with end users. Most of the current studies on Mobile Instant Messaging are focused on only one application at a time and in a specific region of the world. This experiment originally measures over four apps: Three in-market apps (apps with good usability results, selected from previous studies) and one app developed following usability recommendations. In addition, this research originally adds to the current literature results with participants from two different countries. The results show, as practical implications, that the application of specific usability recommendations for Mobile Instant Messaging applications (eg, adding a new contact only with the ID, or providing a visual distinction between individual and group chats, among others) significantly facilitates user performance with these applications. However, further dissemination is needed among researchers and developers. The findings on user behaviour show that the number of close contacts using a particular Mobile Instant Messaging application strongly determines the user’s intention to continue using an application. And not the features offered or the acceptance of the user interface, as most current studies suggest.
Keywords: Usability recommendations; Mobile instant messaging; Mobile app; User behaviour; User performance